2014
DOI: 10.1364/ol.39.003986
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-coding technique for inexpensive and robust retinal imaging

Abstract: We propose a hybrid optical-digital imaging system that can provide high-resolution retinal images without wavefront sensing or correction of the spatial and dynamic variations of eye aberrations. A methodology based on wavefront coding is implemented in a fundus camera in order to obtain a high-quality image of retinal detail. Wavefront-coded systems rely simply on the use of a cubic-phase plate in the pupil of the optical system. The phase element is intended to blur images in such a way that invariance to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
1
18
0
2
Order By: Relevance
“…It has been recently shown 15) that a phase plate fabricated poly(methyl methacrylate) (PMMA) and polished in trefoil shape with a large sag generates not only trefoil phase but also a significant amount of spherical aberration. The results also showed that the WFC system tolerates spherical aberration through a given defocus range but the effect of the spherical aberration in color images was not studied in depth.…”
Section: Shape Of Phase Mask and Aberration Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…It has been recently shown 15) that a phase plate fabricated poly(methyl methacrylate) (PMMA) and polished in trefoil shape with a large sag generates not only trefoil phase but also a significant amount of spherical aberration. The results also showed that the WFC system tolerates spherical aberration through a given defocus range but the effect of the spherical aberration in color images was not studied in depth.…”
Section: Shape Of Phase Mask and Aberration Analysismentioning
confidence: 99%
“…Here we will use the parameters of the optical system proposed in Ref. 15 to obtain retinal images at 633 nm, and therefore, we will assume α = 152 µm, and the lens that focuses images onto the CCD is placed at the exit pupil of the system, with an aperture of 1 cm and a focal length of 25 cm. Simulations with Zemax 28) for different values of A provides the Zernike coefficients of the wavefront at the exit pupil.…”
Section: Shape Of Phase Mask and Aberration Analysismentioning
confidence: 99%
See 3 more Smart Citations